Fiscal sustainability hypothesis test in Central and Eastern Europe: A panel data perspective - Benjamin Owusu (Central European Economic Journal (CEEJ), 2021)
This paper assesses the fiscal sustainability hypothesis for 10 Central and Eastern European countries (CEEC) between 1997 and 2019. The study adopts very recent panel econometric techniques which accounts for issues of structural breaks and cross-sectional dependence in the data generating process to examine the cointegration between government revenue and expenditures. Preliminary results show that revenues and expenditures do not have a long-run relationship and hence a rejection of the sustainability hypothesis. As a next step, we discriminate between structural and cyclical components of revenues and expenditures in order to place emphasis on the structural component. We argue that the structural component of fiscal variables represents the actual long term behaviour of the policymaker. Further results indicate that structural revenues and expenditures have a long-run relationship however with a slope coefficient less than unity which implies sustainability in the weaker sense. At that point, expenditures exceed revenues and if this continues for a long time the government may find it difficult to market its debts in the long run. This result suggests that the fiscal authorities in CEEC must therefore do more by taking long term actions to counteract the rising fiscal deficit problems.
Keywords: H0; H6; E6; 330; Fiscal Sustainability; Cointegration; Government Revenue; Government Expenditure